1982
DOI: 10.1111/j.1528-1157.1982.tb05053.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evolution and Prognosis of Childhood Epilepsies

Abstract: Five-hundred twelve epileptic children were followed longitudinally for several years. The 2- and 4-year remission statuses at the latest examination were 50.6 and 44.2%, respectively. Dividing our sample into groups showing onset of seizures in infancy or at 2-3, 4-7, 8-10, or 11-14 years, the remission rates were as follows: 48.5, 67.6, 49, 46, and 33.3%. The rates of remission of generalized and focal epilepsies were similar (52.9 and 49.7%, respectively; chi 2 = 0.293; p greater than 0.5). The earlier the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
3

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 12 publications
8
21
3
Order By: Relevance
“…While Annegers et al [2] found remission rates higher in patients with generalized seizures than in sub jects with seizures that were focal at onset in their idiopathic group, in our patient popula tion the seizure type did not influence the out come of clinical control. This finding is in agreement with another report which grouped together all epilepsy syndromes in children [15], Partial seizures had a worse prognosis also in the Elwes study [4], and the co-exis tence of several main types of seizures led to a less favourable outcome in an incidence co hort of children without neurodeficit aged 0-19 years and in other studies [16,17], On the other hand, the lack of effect of partial versus generalized seizures in our study can not be related to the proportion of cases with benign rolandic epilepsy. There is no general agree ment on the prognostic value of age at the onset of epilepsy.…”
Section: Prognosis Of Childhood Epilepsysupporting
confidence: 83%
“…While Annegers et al [2] found remission rates higher in patients with generalized seizures than in sub jects with seizures that were focal at onset in their idiopathic group, in our patient popula tion the seizure type did not influence the out come of clinical control. This finding is in agreement with another report which grouped together all epilepsy syndromes in children [15], Partial seizures had a worse prognosis also in the Elwes study [4], and the co-exis tence of several main types of seizures led to a less favourable outcome in an incidence co hort of children without neurodeficit aged 0-19 years and in other studies [16,17], On the other hand, the lack of effect of partial versus generalized seizures in our study can not be related to the proportion of cases with benign rolandic epilepsy. There is no general agree ment on the prognostic value of age at the onset of epilepsy.…”
Section: Prognosis Of Childhood Epilepsysupporting
confidence: 83%
“…In our study, the prognosis after 2 years was good in almost 60% and poor in -30%. One may expect the proportion with a poor outcome to become smaller after longer follow-up, in accordance with the results of earlier studies (4,7,8,23) that concentrated on the long-term outcome. One of the most conspicuous findings of our study is the relatively good outlook early in the course of the disease (i.e., at 2 years of follow-up).…”
Section: Figsupporting
confidence: 78%
“…24 Associations between low IQ and poor seizure control have been found in several studies, [25][26][27][28][29] as has motor disability. 2,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] A significant predictor in this study was multiple types of seizure, a relatively unreported finding. 2,38 It is possible that the average delay of 15 months from seizure onset to assessment allowed time for other seizure types to appear.…”
Section: Discussionmentioning
confidence: 85%